FORMING TEACHERS' POSITIVE ATTITUDES TOWARDS STUDENTS WITH DISABILITIES - Einas SHAMA DANIEL (Moldova State University, 2021)
The current article reflects some results of research that come up with several essential contributions to the implementation of effective integration process within the Physical Education framework, by focusing on the root of altering behaviour - by examining and daring to alter stigmatic attitudes which demand taking responsibility on one's own role as a living model for leading change and eventually, being prepared to restructure the school culture. Based on a special training programme, Physical Education teachers were exposed to and became familiar with the multi-diversity attitude changing model and we could see that they actually became able to reconsider and change their attitudes towards the students, providing live leadership models for their "regular" pupils to keep making change happen.    FORMAREA ATITUDINILOR POZITIVE ALE PROFESORILOR FAŢĂ DE STUDENȚII CU HANDICAP În prezentul articol sunt reflectate câteva rezultate ale cercetărilor care vin cu mai multe contribuții esențiale la implementarea unui proces de integrare eficient în cadrul educației fizice, concentrându-se pe rădăcina modificării comportamentului, examinând și îndrăznind să modifice atitudinile stigmatice pe care le cer, asumându-și responsabilitatea pe propriul rol de model viu pentru conducerea schimbării și, în cele din urmă, pregătit pentru restructurarea culturii școlare. Pe baza unui program special de formare, profesorii de educație fizică au fost expuși și s-au familiarizat cu modelul de schimbare a atitudinii multidiversității. Astfel, constatăm că aceștia au devenit, de fapt, capabili să-și reconsidere și să-și schimbe atitudinea față de studenți, oferind modele de conducere live pentru elevii lor "obișnuiți" să continue să facă schimbarea.